INTEGRATING CIRCULAR ECONOMY PRINCIPLES IN URBAN PLANNING: SUSTAINABLE WASTE MANAGEMENT, RESOURCE EFFICIENCY, AND REGENERATIVE CITY MODELS - Muhammad Sajawal; Nabi Ahmad; Noman Akbar; Dr. Muhammad Ziad (Spectrum of Engineering Sciences, 2025)
This paper focuses on the prospects of implementing circular economy strategies into the urban planning process, such as to advance the concepts of circular waste management, optimize urban resource consumption, and develop the agendas of regenerative cities. Population expansion in cities has led to acceleration in the generation of waste and depletion of natural resources thus calling for change from the linear economy model to the circular economy model. Applying CE principles, municipalities can minimize waste generation, improve the efficient use of the resources, and enable the recycling of waste materials through recycling, waste-to- energy approaches, and the utilization of the used products. The present paper provides an overview of CE, its relation to urban systems, and its application for stimulating innovation and economic growth. It also highlights the politico- organizational barriers, scarcity of funds and low level of awareness regarding CE among the people in urban environments and suggest measures to overcome these drawbacks. The study also shows, in the case of Amsterdam and Copenhagen, how CE can be utilized to enhance urban resilience by making cities more sustainable and yielding good value-added ecological, economic, and social returns.